Mathematics Critical Thinking Ability of Elementary School Students Based On Cognitive Style and Self-Efficacy - Yustitia, Via; Kusmaharti, Dian (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
Learning mathematics does not only teach mathematical concepts, but requires students to encourage critical thinking skills. Critical thinking skills are also 21st century skills that enable students to think reflectively and reason in making decisions. Several factors influence critical thinking, including cognitive style and self-efficacy. The purpose of this study was to analyze: (1) students' critical thinking skills with field dependent and field independent cognitive styles who have high self-efficacy. (2) students' critical thinking skills with field dependent and field independent cognitive styles have low self-efficacy. This research is a qualitative research using the phenomenological method in elementary schools throughout the Gayungan District. Subjects were selected from 14 elementary schools in Gayungan District. Through purposive sampling, students with a certain cognitive style and self-efficacy were selected. The method used in the form of questionnaires, tests, and interviews. The researcher as the main instrument, assisted by cognitive style and self-efficacy questionnaire instruments, critical thinking ability test questions, and interview guidelines. Data analysis used qualitative analysis and the validity of the data used the triangulation method.